Local Government in Britain / Everyone's Guide to How It All Works - Byrne Tony (Penguin Books, 1990)
We all rely on local government to protect us from crime, fire and environmental dangers, to provide education, health care, housing and sport facilities, yet many people are astoundingly ignorant of how it all works. Glossary, Prefaces, Recent Landmarks, What Local Government Is, An Evolving System, The Structure of Local Government, The Functions of Local Government, London's Local Government, Local Government Elections, The Political Parties, The Counsellors, Internal Organization: The Council and Its Committees, Internal Organization: The Officers, Finance, Controls and Influences, Local Government and the Local Community, Into the Nineties: Managing (More) Change, Appendixes, Notes and References, Further Reading, Index.